Training workshop report: Implementing Nationally Determined Contributions (NDC) Commitments in Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The ratification of the Paris Agreement in 2016 laid the course for all countries to set Nationally Determined Contributions (NDCs) for greenhouse gas emissions (GHGs) and adaptation activities and begin implementation of these plans. In many developing countries, the agriculture sector is a key component of mitigation contributions and adaptation plans. However, not all sectoral ministries including, for example the Ministry of Agriculture, have the full knowledge about the UNFCCC processes, the global climate negotiations and their role in contributing to the national commitments in climate change and the NDCs. GIZ, as part of its support to African Union institutions, is working with NEPAD to help support African countries in their implementation of NDC commitments through creation of a training course.